Afghanistan's Neo-Taliban Puzzle. (July 2021) - Wani, Zahoor Ahmad
This article examines the emergence of the neo-Taliban and its encroachment in non-Pashtun regions after the debacle of the old Taliban following the post 9/11 US-led NATO intervention in Afghanistan. It seeks to understand what aspirations drive the neo-Taliban and how they have reframed their ideology after 2001, leading to growing acceptance of a future role for the neo-Taliban in Afghanistan, while foreign-led counterinsurgency seems to fail. The article argues that due to the extremely fractious nature and continuing precariousness of the Afghan political climate, the neo-Taliban could emerge as a formidable power, with an agenda of bringing peace and stability to the entire 'Af-Pak' region. However, to what extent the neo-Taliban may be successful in countering widely held perceptions that it is a Pashtun nationalist movement, antagonistic to women, dissent and minorities, remains part of the challenging puzzle, as much for analysts as for the movement itself, which is not trusted in terms of delivering good governance in Afghanistan.